THE CORRELATION BETWEEN EDUCATION, WORK, AND MATERNAL KNOWLEDGE ON COMPLEMENTARY FEEDING WITH 6-24 MONTHS' NUTRITIONAL STATUS - Alfiana, Dina; Pratiwi, Witri; Sanif, Muhammad Edial (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Indonesian Basic Health Research in 2018 reported that the prevalence of malnutrition in Indonesia was 17.7% which consists of 13.8% malnutrition and 3.9% severe malnutrition. In West Java Province, the prevalence of malnutrition and severe malnutrition is still high at 15.6%. The aim of this study is to examine the correlation between education, work, and maternal knowledge about complementary feeding with baby nutrition status aged 6-24 months.Methodology: This was a cross sectional study. The sample of this study was 100 mothers of infants aged 6 to 24 months in the Tegalgubug Health Center, in Cirebon City which selected by cluster sampling. Data have been collected from questionnaires and anthropometric measurement of weight for age Z (WAZ). Nutritional status was categorized into malnutrition status if z score <-2 SD up to <-3 SD, and good nutrition status if z score -2 SD to 2 SD. The analysis of the study was tested by Spearman correlation.Results: From 100 respondents,51% of them were low educated mother, 55% were working mother, 51% had good knowledge, and 83% had good nutrition?s babies. The bivariate analysis showed that education, working status, and mother?s knowledge about complementary feeding were statistically significant correlated with nutritional status of infants (p=0.021, p=0.020, p=0.013, respectively).Conclusion: Education, working status, and knowledge were significant correlated with nutritional status of infants aged 6 to 24 months. Malnutrition of infants can be greatly reduced by educating maternal about complementary feeding and given accurate information about nutritional status of infants.